MEKANISME KERJASAMA PUSAT PELAPORAN DAN ANALISIS TRANSAKSI KEUANGAN (PPATK) DAN INSTANSI TERKAIT DALAM PENYELIDIKAN PENYIDIKAN TINDAK PIDANA PENCUCIAN UANG - Kartika Sastra, Putu; Swardhana, Gde Made; Surya Darmajaya, Ida Bagus (Kertha Negara : Journal Ilmu Hukum; Vol. 01, no. 01, Maret 2013, 2013)
In Article 40 of the Regulation of the President of the Republic Indonesia No. 50 of 2011 Article 2 paragraph (1) assign tasks to PPATK to the prevention and combating of money laundering. Of this task can take action PPATK suspension of all or part of transactions suspected of being proceeds of crime. Money laundering generally starts from the PPATK provide Financial Intelligence to law enforcement authorities and ask for the development of inquiries and investigations that have been conducted by investigators predicate offenses. Is an investigator of the predicate offense is an officer of the agency by law is given the authority to conduct an investigation, the Indonesian National Police, the Attorney General, the Corruption Eradication Commission (KPK), the National Narcotics Agency (BNN), and the Directorate General for Taxation and Directorate General of Customs and Excise, Ministry of Finance of the Republic of Indonesia.
Keywords: PPATK, Financial Intelligence, Investigator Of The Predicate Offense.